EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD PADA PEMBELAJARAN IPAS DI SD 030342 SILALAHI - Opris Sianipar; Frida Marta Argareta Simorangkir; Antonius Remigius Abi; Eka Margareta Sinaga; Paska Sriulina Tarigan; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the Think Pair and Share (TPS) type cooperative learning model assisted by Wordwall media on critical thinking skills of grade IV elementary school students in IPAS learning at SD 030342 Silalahi in the 2024/2025 academic year. This study used an experimental method with a One-Group Pretest-Posttest design. The research sample amounted to 30 fourth grade students. The instruments used were a description test to measure students' critical thinking skills before and after treatment, and a questionnaire to determine students' responses to the learning model used. The results showed that there was a significant increase in students' critical thinking skills after applying the TPS learning model assisted by Wordwall. The average pretest score of 55.73 increased to 79.86 in the posttest. The N-Gain test showed an increase of 0.69 (moderately effective category). The correlation coefficient test results show the value of r_hitung = 0.610 is greater than r_table = 0.339, which means there is a strong relationship between the application of the TPS model assisted by Wordwall with students' critical thinking skills. Furthermore, the t-test results obtained t_hitung = 4.357 and t_table = 1.690, so t_hitung ≥ t_table (4.357 ≥ 1.690). Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is a positive and significant influence between the application of the Think Pair and Share (TPS) type cooperative learning model assisted by Wordwall on improving students' critical thinking skills in IPAS learning.